Diseño y construcción de un módulo de inversión monofásico multinivel de 3 etapas y 27 niveles para el laboratorio de electrónica de potencia. - Tapia Hidalgo, Dayana Noemi (2018)
This project indicates the design and construction of a multilevel inverter module with 3 stages and 27 levels. It is built in bridge H cascade configuration with common source, and converts direct current into alternating current by switching power transistors (IGBT's). Through the rectification of each stage, different waveforms are obtained, which when added through transformers reconstructs a sinusoidal signal of 27 levels with a peak output voltage of 110Vac at a frequency of 60 Hz. Within the control phase, AVR was programmed to generate the trigger signals that are sent to the signal isolator circuit formed by optocouplers (6N137) to separate the control stage from the disturbances generated in the power stage. For the power stage, a switching circuit formed by the IR2110 drivers was implemented to stabilize the pulses at the same voltage level and to ensure the triggering of the power switches. Three H bridges with IGBTs were also implemented to rectify and add up their resulting waves to obtain the sinusoidal signal reconstructed by means of transformers. A didactic module was built to observe the resulting sinusoidal output at 27 levels, which can be connected to a resistive, resistive-inductive load and a single-phase motor of ¼ HP and 110Vac. Finally, a technical manual for the module and a laboratory practice were prepared to better understand the operation of the investor.